Порівняльний аналіз результатів експериментальних та теоретичних досліджень робочих процесів в гідрооб'ємно-механічних трансмісіях - Бондаренко, Анатолій Ігорович (Луцький національний технічний університет, 2015)
В роботі визначено вплив законів зміни параметрів регулювання гідромашин гідрооб'ємної передачі та законів зміни гальмівного моменту на основні параметри гідрооб'ємно-механічних трансмісій різних структур (розглядалися дві схеми: одна з диференціалом на вході, друга -з диференціалом на виході) при реалізації процесу гальмування, а також проведено порівняльний аналіз теоретичних результатів з експериментальними.

In work certainly influence of laws of change of parameters of adjusting of hydraulic machine hydrostatic transmission and laws of change of brake moment on the basic parameters of hydrostatic-mechanical transmission of different structures (two charts were examined: one with a differential on the entrance, second -with a differential on an output) during realization of braking process. Set, how intensity of change of parameter of adjusting of hydraulic machine and change of brake moment influences on the overfall of working pressure in the hydrostatic transmission, angular speeds of billows, time, from the beginning of braking to to the complete stop of billow of powder-like brake mechanism. The got results areanalysed, comparison of theoretical results is made with experimental, an error is set boundary path by the maximal values of overfall of working pressure in the hydrostatic transmission, by twisting moments on the billows of transmissions and angular speeds of billows. A conclusion is done about expedience of the use of the examined mathematical model describing the dynamics of process of braking of hydrostatic-mechanical transmission.
Comparative analysis of results of experimental and theoretical researches of working processesin hydrostatic-mechanical transmission
Keywords: експериментальне дослідження; гідрооб'ємна передача; гальмування; математична модель; процес гальмування; experimental research; hydrostatic transmission; braking